Memory Crash Politics of History in and around Ukraine, 1980s-2010s - Kasianov, Georgiy (Central European University Press, 2022)
This account of historical politics in Ukraine, framed in a broader European context, shows how social, political, and cultural groups have used and misused the past from the final years of the Soviet Union to 2020. Georgiy Kasianov details practices relating to history and memory by a variety of actors, including state institutions, non-governmental organizations, political parties, historians, and local governments. He identifies the main political purposes of these practices in the construction of nation and identity, struggles for power, warfare, and international relations. Kasianov considers the Ukrainian case in the context of a global increase in the politics of history and memory, with particular emphasis on a distinctive East-European variety. He pays special attention to the use and abuse of history in relations between Ukraine, Russia, and Poland.